MANAJEMEN ORGANISASI BERBASIS ETIKA BISNIS ISLAM PADA PERUSAHAAN TEKNOLOGI: STUDI DAMPAK AKUISISI GoTo-GRAB - Titin Windiasari; Kukuh Tondoyekti; Mariana, Mariana; Selamat Riadi (Yayasan Nusantara Hasana Berdikari, 2025)
The proposed acquisition of PT GoTo Gojek Tokopedia Tbk by Grab Holdings Limited has raised significant concerns in Indonesia, including operational disruptions, mass layoffs, employee demotivation, organizational cultural conflicts, and threats to national identity as a symbol of digital independence. This study examines the application of Islamic Corporate Governance, grounded in the principles of amanah, adalah, and ihsan, to address these challenges within the context of innovative companies often constrained by rigid management structures. Utilizing document analysis and Decision Tree Analysis, the study reveals that the acquisition could have a substantial impact, with an average impact score of 41.8 out of 100. The Islamic Corporate Governance framework offers solutions through transparent communication, fair policies, and the preservation of local values, enhancing stakeholder trust and Indonesia’s digital sovereignty. This research introduces an innovative approach by integrating Islamic ethics into technology acquisition management, balancing business efficiency with social responsibility.